Study of Endometrial Pathology in Abnormal Uterine Bleeding Patients Visited in Hospital: An Retrospective Study - Kheta Ram Soni; Sudesh Agarwal (Asian Journal of Medical Research, 2019)
Background: Abnormal uterine bleedingis the commonest presenting symptom in gynaecology out-patient department. This retrospective study was done to assess the incidence of endometrial pathology in abnormal uterine bleeding patients visited in hospital.Subjects and Methods:This was a prospective study done on patients presenting with abnormal uterine bleeding from done in the Department of Obstetrics & Gynecology, Government Medical College, Barmer, Rajasthan, India. The study sample included a total number of 440 women. Specimens were fixed in 10% formalin, processed, embedded in paraffin and 3- 4 micron thick sections were cut and stained with H&E. Histological evaluation was done. Results:In the present study total no. of cases were 440 in which maximum cases had isolated endometrial pathology (69.09%). Maximum no. of patients had menorrhagia (38.63%). 29.77% patients had metrorrhagia.Conclusion: Endometrial cause of AUB is age related pathology. In our study maximum cases had isolated endometrial pathology and maximum no. of patients had menorrhagia.